2020
DOI: 10.17706/jcp.15.2.37-47
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Critical Success Factors for CD-ERP Model

Abstract: Collaboratively-Developed ERP (CD-ERP) is an intermediate model between two well-known models, namely: closed-and open-source systems. This model is based on the community-source paradigm and ERP packages. It has been proposed for Libyan higher education (LHE) to be governed by a consortium of LHE institutions. To investigate the applicability of this model in LHE, this paper presents an analysis of critical success factor (CSFs) based on both a review of the relevant literature and lessons learnt from similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…As illustrated in Figure 1, the authors examined: firstly the Libyan side, in terms of IS performance, the capability to develop ISs, and other aspects of LHE at university level. The results of the fieldwork in Libya can be found in (Almigheerbi, Ramsey, and Lamek, 2019) (Almigheerbi et al, 2020), while other publications on the topic of the CD-ERP model can be found in (Almigheerbi, Ramsey and Lamek, 2020a, 2020b, 2020c and. Secondly the international side was studied in terms of how such ISs have been implemented and what can be learnt from these experiences.…”
Section: Methodsmentioning
confidence: 99%
“…As illustrated in Figure 1, the authors examined: firstly the Libyan side, in terms of IS performance, the capability to develop ISs, and other aspects of LHE at university level. The results of the fieldwork in Libya can be found in (Almigheerbi, Ramsey, and Lamek, 2019) (Almigheerbi et al, 2020), while other publications on the topic of the CD-ERP model can be found in (Almigheerbi, Ramsey and Lamek, 2020a, 2020b, 2020c and. Secondly the international side was studied in terms of how such ISs have been implemented and what can be learnt from these experiences.…”
Section: Methodsmentioning
confidence: 99%